Making moves : an adventure through space, colour & form : an exegesis presented with exhibition as fulfilment of the requirements for thesis Masters of Fine Arts at Massey University, Wellington, New Zealand - Peters, Gary C G (Massey University, 2012)
This exegesis reveals a practice that has been driven by making as the means to address questions concerning colour, space, form, time and site. From an initial desire to create a sustainable and self generating painting practice this text plots the development of a systematic method that uses data derived from choose-your-own-adventure books. As the system is deployed across a variety of sites, wall drawing and paper folding become the focus where the rules based generation of form is fused with an intuitive sense of placement and use of colour. Further deployment explores the role of colour in response to site, the temporal nature of this work and it’s engagement with the viewer resulting in a response to architectural site.
Keywords: Criticism and interpretation; Mural painting and decoration; Wall drawings; Helio Oiticica; Peter Halley; Sol LeWitt; Colour; Site; Space and time; Choose-your-own-adventure; Pick-a-path; Games; Temporal; Richard Wright